Measuring quality in cancer care: overview of initiatives in selected countries. (28th June 2013) - Wild, C.; Patera, N.
Abstract : To inform the Austrian National Cancer Plan on possible generic quality indicators that might be derived from routine data a systematic literature search in three databases, followed by extensive hand‐searching to locate initiatives and their publications was carried out in spring 2011. Twenty‐one initiatives that developed indicators for measuring quality of cancer care were identified: longer standing and decentralised initiatives are characteristics of the USA. The Canadian province of Ontario publishes the Cancer System Quality Index, centralised audit and peer review programmes are undertaken in the National Health Service in the UK. Methodologically sound cancer type‐specific pilot projects in Belgium have been implemented, the Netherlands and Denmark are running national initiatives. Germany recently started quality measurement activities, too. Generic indicators often focus on end‐of‐life care, multidisciplinarity, advance care planning and documentation. Indicators measuring the quality of care during an entire episode of cancer are rare, as are those for less common cancers and for care in the outpatient setting. Access, equity and the patient's perspective are only beginning to be incorporated into indicators. After having identified a range of candidate indicators that can be implemented with routinely collected data alone, piloting them in Austria would be the next step to go.